MARKETING PUBLIC RELATIONS KARAOKE HAPPY PUPPY BANJARMASIN DALAM MENARIK MINAT PENGUNJUNG - Sri Waryuni; Rahmi Widyanti; Zain Noktah Aslie (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2016)
The purpose of this study was to determine how marketing public relations of Happy Puppy Banjarmasin karaoke in an effort of attracting visitors.The method used in this study is a qualitative research method, this method is trying to describe and explain an event by looking at the facts that exist as observations, but researcher also analyze and integrate, after that researcher conducted a classification. Data collection methods that writer use are interviews and documentaries.These results indicate that marketing public relations conducted by Happy Puppy Banjarmasin in an effort of attracting visitors through activities, namely: 1) Corporate identity, 2) sponsorship, 3) community relations 4) Publications, and 5) Customer relations, those activities through the phases of planning, implementation, and evaluation in accordance with the opinion of Ruslan (2010), and from 7 marketing public relations activities mentioned by Kasali (2006) only 4 marketing public relations activities undertaken by Happy Puppy Banjarmasin.